A Descriptive study on the process of prenda among the dulangan manobo of Lageton Barangay Tinalon, Kulaman, Sultan Kudarat - Ganir, Eula V.
This study entitled ?a descriptive study on the process of prenda among the Dulangan Manobo of Lageton Barangay Tinalon Kulaman, Sultan Kudarat presents what prenda is, the process involved, and the reasons behind the prevalence of prenda. The location of the study is in Kulaman, Sultan Kudarat particularly in Sitio Lageton, Barangay Tinalon. Primary data were gathered through interviews using survey questionnaire. Library research primarily from published literature and journals were also conducted. This paper is a descriptive study of prenda, a cebuano term referring to transferring of ?right-to-use? or cultivate an area. There are three reasons behind the prevalence of prenda, payment of debt from gambling, payments for hospitalization and procurement of bride price (sunggod). The prevalence of prenda is a clear indicator that land is individually owned contrary to the commonly held assumption that indigenous people such as the Dulangan Manobo, view land as communal property. Although, there is a subdivision of land ownership this does not mean that the Dulangan Manobo neglect the concept of collective ownership of land. It is important to emphasize that within the domain of the Dulangan Manobo land is communally exclusive to them however, they recognize individual land ownership within the bounds of the shared domain.